Antimicrobial activities of Plumeria alba extracts - Omar, Muhammad Nor; Mohamad Nor, Maryana; Darnis, Deny Susanti; Zuberdi, Ahmad Muzammil (2011)
Plumeria alba (Apocynaceae) has been traditionally used as medicine for the treatment of ulcers, herpes and scabies. The plants were extracted using various solvents, i.e. hexane, ethyl acetate, dichloromethane and methanol. In addition, the cold water extraction was also performed to obtain the aqueous extract. The phytochemical screening of the crude extracts revealed the presence of tannins, saponins, flavonoids, steroids, terpenoids, cardiac glycosides, phytosteroid and reducing sugar. The antimicrobial activity of each crude extract was determined using the disc diffusion method for Fusarium solani, Aspergillus niger, Candida albicans, Saccharomyces cerevisae, Pseudomonas aeruginosa, Bacillus subtilis and Bacillus cereus. The results showed that the ethyl acetate extracts of the flowers and leaves were very potent in inhibiting A. niger, S. cerevisae, P. aeruginosa and B. cereus with the zone of inhibition diameters ranging between 7mm and 15mm. Meanwhile, the inhibition diameters of methanolic extract from the stems and leaves were between 8mm and 11mm, but B. Subtilis showed no resistance to all extracts.